Synthesis of Potentially Bioactive Carbohydrate Derivatives by Chemoslective Hydrogenation with PdFe Catalyst. Issue 48 (20th December 2019) - Rojas, Agustín H.; Zendri, Lucía Garritano; Lafuente, Leticia; Ponzinibbio, Agustín; Vetere, Virginia
Abstract: A highly efficient and chemoselective hydrogenation method was developed using a bimetallic PdFe catalyst. Pd and Ni catalysts failed in the tests performed. However, PdFe supported on carbon catalyst (10% w/w Pd and a molar ratio Fe/Pd=0.5) achieved interesting results. The selective nitro and aldehyde group reductions on the aromatic aglycone moiety were satisfactory. The desired products were obtained with high conversion and selectivity. A set of aryl O‐glycosides, such as bioactive Gastrodin, were prepared in very good yields and high β‐anomeric selectivity. Abstract : A highly efficient and chemoselective hydrogenation method was developed using PdFe supported on carbon catalyst (10% w/w Pd and a molar ratio Fe/Pd=0.5). The selective nitro and aldehyde group reductions on the aromatic aglycone moiety were satisfactory. The desired products were obtained with high conversion and selectivity in very good yields and high β‐anomeric selectivity.